The Pastoral Care for Catholics According to The Spirit of Charity of Priests Under The Thai Missionary Society. - Namwong, Rev.Apichart; Phongsiri, Rev.Asst.Prof.Dr.Chartchai; Saengthien, S.J., Rev.Dr.Pichet; Prasutsaengchan, Asst.Prof.Dr.Laddawan (Saengtham College Journal, 2021)
Objectives of research for The Pastoral Care for Catholics according to The Spirit of Charity of Priests under The Thai Missionary Society The objectives of this research were to find : (1) the pattern of the pastoral care and the evangelization of priests under the Thai Missionary Society in the present society and (2) the relationship between the pastoral care with the spirit of charity and the mission of priests under the Thai Missionary Society in the present society. Informants for this research were all priests of the Thai Missionary Society who were working in Thailand, total seven respondents. The instrument used in this research was a semi-structured interview and content analysis. The results of this research were : The pattern of the pastoral care and the evangelization of priests of the Thai Missionary Society, according to the mission area in the present society context, was proclaiming the Good News of the Lord Jesus Christ to ethnic groups, non-Catholic and those who were in difficult situations. Love of Christ was the inspiration and basis of spiritual motivation to proclaim the Good News of this apostolic family by cooperating and uniting with the local Church, through various rituals and activities which were suitable for ethnic groups and respectful of local cultures. The pastoral care with the spirit of charity is related with the mission of priests of the Thai Missionary Society in the present society. The pastoral care is focused on the charity, which conform to the mission of the Thai Missionary Society to proclaim the Good News to ethnic groups, non-Catholic and those who were are difficult situations, without exception of to the race or religion. This involves support for the poor, the disabled, the sick, the elderly abandoned, the orphans and the marginalized and all those in need. This charity is exercised with self - sacrifice, humility, and poverty by regardless of personal interests in imitation of Christ in the proclamation of the Good News and the witness of life.